2021
DOI: 10.1101/2021.06.08.447518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic multi-omics cell line profiling uncovers principles of Ewing sarcoma fusion oncogene-mediated gene regulation

Abstract: Cell lines have been essential for major discoveries in cancer including Ewing sarcoma (EwS). EwS is a highly aggressive pediatric bone or soft-tissue cancer characterized by oncogenic EWSR1-ETS fusion transcription factors converting polymorphic GGAA-microsatellites (mSats) into neo-enhancers. However, further detailed mechanistic evaluation of gene regulation in EwS have been hindered by the limited number of well-characterized cell line models. Here, we present the Ewing Sarcoma Cell Line Atlas (ESCLA) comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…This indicates that FEZF1 is highly expressed in Ewing sarcoma cells and that FEZF1 expression was specific for Ewing sarcoma, at least when compared to other bone sarcomas. To strengthen these results, we analyzed the datasets available from a study published during the preparation of this manuscript and in which the authors carried out a multi-omics approach to characterize an extensive list of Ewing sarcoma cell lines [ 30 ]. According to this study, FEZF1 is expressed at high levels in all Ewing sarcoma cell lines studied, including cells expressing EWSR1-FLI1 and EWSR1-ERG fusion proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This indicates that FEZF1 is highly expressed in Ewing sarcoma cells and that FEZF1 expression was specific for Ewing sarcoma, at least when compared to other bone sarcomas. To strengthen these results, we analyzed the datasets available from a study published during the preparation of this manuscript and in which the authors carried out a multi-omics approach to characterize an extensive list of Ewing sarcoma cell lines [ 30 ]. According to this study, FEZF1 is expressed at high levels in all Ewing sarcoma cell lines studied, including cells expressing EWSR1-FLI1 and EWSR1-ERG fusion proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we asked how many genes on this list had GGAA microsatellites bound by EWSR1-FLI1 and, in this way, determined whether these genes were directly regulated by EWSR1-FLI1 or by FEZF1. For that purpose, we searched the list of 67 genes for EWSR1-FLI1 peaks at a maximum of 10 kb upstream and downstream TSS using an in-house R script and the list of EWSR1-FLI1 ChIP-seq binding sites coincident with the GGAA microsatellites described in Orth et al [ 30 ]. We found that no FEZF1/EWSR1-FLI1 regulated genes had a peak of 10 Kb upstream TSS and only two genes (FEZF1 and PHOSPHO1) had a peak 10 Kb downstream TSS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations